Identifikasi Kondisi Fisik Lingkungan Kerja Pada PT. Tribuana Multitaria Hotel Santika Ambon - Ira Sandi Tunny (Lembaga Pengembangan Kinerja Dosen, 2024)
The prevalence of work-related accidents, which is still quite high, is a natural health issue that primarily affects individuals of all ages in both developed and developing nations. The purpose of this evaluation is to determine the working conditions at PT. Tribuana Multitaria Santika Ambon. The estimating techniques used in this kind of research are fascinating. The workspace of PT. Tribuana Multitaria Santika Ambon employees The research population was lodgings. There were five sample points measured in each room. After being gathered, data is legitimately examined, and then it is automatically processed. Following expressive checking, the loop is shown as a table. For every position, a temperature of around 270 degrees Celsius satisfies the criteria.